Mini's Money - Nandini Nayar (Bharat Harper Collins, 2019)
Nandini Nayar s Mini s Money, the first in the new Mini series of chapter books, is about a five-year-old girl who is gifted some money on Dussehra. The money goes where Mini goes and Mini goes where the money goes as everyone wonders what Mini will spend it on. After some exciting adventures following her money, Mini knows how she is going to spend it. Her family is surprised when they see where Mini s money is going and how Mini will soon have to follow it there! A delightful story, charmingly illustrated and perfect for the Diwali season.
Keywords: Realistic Fiction -- Realistic Fiction